SOX11 and SOX4 drive the reactivation of an embryonic gene program during murine wound repair - Miao, Qi; Hill, Matthew C.; Chen, Fengju; Mo, Qianxing; Ku, Amy T.; Ramos, Carlos; Sock, Elisabeth; Lefebvre, Véronique; Nguyen, Hoang (Nature Communications, 2019)
Tissue injury induces changes in cellular identity, but the underlying molecular mechanisms remain obscure. Here, we show that upon damage in a mouse model, epidermal cells at the wound edge convert to an embryonic-like state, altering particularly the cytoskeletal/extracellular matrix (ECM) components and differentiation program. We show that SOX11 and its closest relative SOX4 dictate embryonic epidermal state, regulating genes involved in epidermal development as well as cytoskeletal/ECM organization. Correspondingly, postnatal induction of SOX11 represses epidermal terminal differentiation while deficiency of Sox11 and Sox4 accelerates differentiation and dramatically impairs cell motility and re-epithelialization. Amongst the embryonic genes reactivated at the wound edge, we identify fascin actin-bundling protein 1 (FSCN1) as a critical direct target of SOX11 and SOX4 regulating cell migration. Our study identifies the reactivated embryonic gene program during wound repair and demonstrates that SOX11 and SOX4 play a central role in this process.
CRIS-Team Scopus Importer:2019-09-17